ANALISIS DAN PERANCANGAN ALAT PENGENDALI E- ANNOUNCEMENT - Rini Suwartika (INFOKOM (Informatika & Komputer), 2018)
This research was aimed to design of control device e-announcemnet using sms gateway at Puslitbang tekMIRA. Based on the last research result, at Puslitbang tekMIRA it has not used device and system for announcement update. Therefore, need to have a new device and system design with a more integrated database system which makes announcemnet update becomes more effective. The development method that is used in this research is using the Waterfall method which is implemented with C language, Microsoft Visual Studio Language Program, and Microsoft Access as the database system. There are some suggestions for solving those problems there are: using device and the computerized system; developing system in the future;and maintaining the system routinely.